Perancangan Sistem Informasi Pembinaan Atlet Dojang Taekwondo Pada Jasdam II Sriwijaya - elitaputri10_ putri; Tata Sutabri (PPPM Institut Teknologi Pagar Alam, 2025)
The development of information technology has made a significant contribution to the world of sports, especially in improving the effectiveness of the athlete development process. At the Jasdam II Sriwijaya Taekwondo Dojang, the assessment and monitoring of athlete development remains a challenge, leading to inaccurate and inefficient coaching evaluations. This study aims to design an Athlete Development Information System based on the Extreme Programming (XP) method, allowing application development to run iteratively and in accordance with user needs. With this system, coaches, athletes, and parents can record training progress by providing assessments, and manage training schedules automatically and in an integrated manner. The system implementation can improve the quality of athlete development, facilitate more systematic and accurate progress monitoring, and increase efficiency in managing scores and schedules. Ultimately, the application of this technology supports the improvement of athlete performance through more structured and targeted evaluations. The results of application testing using the black-box testing method indicate that all system features function according to their functions without errors in the operational process. The testing covers all menus for coaches and athletes, from the login process, inputting scores, displaying progress charts, managing training schedules, to updating profiles, and all of which function as expected (successful).